The climate change imaginary. (March 2015) - Luke, Timothy W
Climate change is represented as an increasingly conventionalized cluster of signs, symbols, and stories. This symbolic formation typically is cast in various graphic and tabular presentations of how greenhouse gases are disrupting Nature and its environments. The essentially contested quality of this imaginary, and its conflicting characteristics, force one to re-examine how mediated, constructed, and rhetorical these depictions are. Such aesthetic constructs are a risky art in which climate change images can circulate as illusion, ideology, and invention as well as factual and functional scientific findings. Rather than being simple presentations of Nature as such, these efforts are often complex representations of social forces with political agendas. Presentations of these imaginaries as well as reactions to them leave one pondering how the images serve many purposes: to discredit or validate the still emerging sciences for modeling, monitoring, and managing climate change; to legitimize or forestall ongoing debates about climate change and its causes; or to aestheticize or paralyze thinking about global warming as the sheer immensity, root uncertainty, and clear complexity of taking any action grip both the elites and publics.